2016
DOI: 10.1002/da.22471
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Remission After Prolonged Exposure Treatment Is Associated With Anterior Cingulate Cortex Thinning and Volume Reduction

Abstract: Background Brain structures underlying posttraumatic stress disorder (PTSD) have been a focus of imaging studies, but associations between treatment outcome and alterations in brain structures remain largely unexamined. We longitudinally examined the relation of structural changes in the rostral anterior cingulate cortex (rACC), a previously identified key region in the PTSD fear network, to outcome of Prolonged Exposure (PE) treatment. Method The sample included 78 adults (53 women): 41 patients with PTSD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
(82 reference statements)
3
23
0
Order By: Relevance
“…We previously reported functional (Helpman, Marin, et al, 2016) and structural (Helpman, Papini, et al, 2016) PE-related changes in this sample. This report presents their rsFC findings.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…We previously reported functional (Helpman, Marin, et al, 2016) and structural (Helpman, Papini, et al, 2016) PE-related changes in this sample. This report presents their rsFC findings.…”
Section: Methodsmentioning
confidence: 75%
“…Psychotherapy research in posttraumatic stress disorder (PTSD) has recently begun using neuroimaging methods to assess structural (Helpman, Papini, et al, 2016) and functional (Fonzo, Goodkind, Oathes, Zaiko, Harvey, Peng, Weiss, Thompson, Zack, Lindley, et al, 2017; Helpman, Marin, et al, 2016) neural alterations of evidence-based treatments. Prolonged Exposure (PE) therapy is a relatively brief, highly structured, exposure-based treatment, considered to be effective in treating PTSD (Bradley, Greene, Russ, Dutra, & Westen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although most PTSD treatments to date have focused on normalizing fear network deficits (Foa et al, 2005, Helpman et al, 2016b, our findings suggest that when PTSD patients have comorbid MDD, as is common (Neria & Bromet, 2000), they may benefit from a more comprehensive treatment approach addressing impairments in both fear and reward processing. Previous treatment studies have demonstrated efficacy in depression for treatments that putatively address reward dysfunction, such as behavioral activation (Dimidjian et al, 2006) and dopaminergic drugs (Soskin, Holt, Sacco, & Fava, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Some studies demonstrated a negative correlation between cortical thickness and PTSD severity (Corbo et al, 2014; Lindemer et al, 2013; Liu et al, 2012; Sadeh et al, 2016). Greater cortical thickness was previously associated with resilience and enhanced recovery from PTSD symptoms (Dickie et al, 2013; Lyoo et al, 2011; Nilsen et al, 2016), although not without inconsistencies (Helpman et al, 2016). …”
Section: Introductionmentioning
confidence: 97%